2013
DOI: 10.1152/ajprenal.00639.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inherited secondary nephrogenic diabetes insipidus: concentrating on humans

Abstract: The study of human physiology is paramount to understanding disease and developing rational and targeted treatments. Conversely, the study of human disease can teach us a lot about physiology. Investigations into primary inherited nephrogenic diabetes insipidus (NDI) have contributed enormously to our understanding of the mechanisms of urinary concentration and identified the vasopressin receptor AVPR2, as well as the water channel aquaporin-2 (AQP2), as key players in water reabsorption in the collecting duct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 65 publications
1
40
0
Order By: Relevance
“…There are primary and secondary forms of inherited NDI [2]. In primary inherited NDI, we distinguish between an Xlinked form, due to mutations in the gene encoding the vasopressin type 2 receptor, namely arginine vasopressin receptor-2 (AVPR2) and an autosomal form, due to mutations in the gene encoding the water channel aquaporin2 (AQP2).…”
Section: Introductionmentioning
confidence: 99%
“…There are primary and secondary forms of inherited NDI [2]. In primary inherited NDI, we distinguish between an Xlinked form, due to mutations in the gene encoding the vasopressin type 2 receptor, namely arginine vasopressin receptor-2 (AVPR2) and an autosomal form, due to mutations in the gene encoding the water channel aquaporin2 (AQP2).…”
Section: Introductionmentioning
confidence: 99%
“…110 were found, whereas in others, the phenotype was not detailed enough to clearly establish a diagnosis of NDI. 56 In a Japanese study no mutations were identified in 7 of 62 (11%) families with clinical NDI, 34 suggesting that genes other than AQP2 and AVPR2 might be involved. However the phenotypes of these patients were poorly described and not further investigated by the referring physicians.…”
Section: [H2] Prostaglandin Synthesis Inhibitorsmentioning
confidence: 97%
“…55,56 These patients have Mendelian diseases that affect tubular function with NDI as a secondary complication. In some such patients the NDI symptoms dominate the clinical picture, leading to an initial misdiagnosis, with the true underlying cause of disease subsequently identified.…”
Section: [H1] Secondary Inherited Forms Of Ndimentioning
confidence: 99%
“…Moreover, this pathway may be involved in some of the secondary forms of NDI, seen in disorders with hypercalciuria, such as Bartter syndrome [21,22]. However, luminal calcium concentrations in concentrated urine are typically much higher than those seen in the dilute urine of patients with secondary NDI, raising questions about the clinical relevance of this pathway [23,24].…”
Section: Calcium Sensing Receptormentioning
confidence: 99%
“…Indeed, potassium deprivation in rats is associated with polyuria and decreased Aqp2 expression, through yet unidentified mechanisms [28]. But yet again, the clinical relevance in man is unclear, considering that patients with Gitelman syndrome have hypokalemia, but an apparent normal urinary concentrating ability [23].…”
Section: Hypokalaemiamentioning
confidence: 99%